Legal regulation of tourism: experience and prospects - Mukasheva, A.A.; Ybyray, N.U. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
This article examines the issues of existing international and national experience in the field of legal regulation of tourism in the post-pandemic world. The main stages of development of legislation on tourism in the Republic of Kazakhstan have been formed, which is one of the fundamental conditions for the formation of a separate branch of tourism law. The article provides examples of international regulation of the tourism sector, as well as models of state policy regarding the development and stimulation of tourism activities. Thus, theanalysismadea certain contributions to the theoretical foundations of tourism law.